Do recycled spectacles meet the refractive needs of a developing country?. (25th November 2014) - Wan, Sue Ling; Yazar, Seyhan; Booth, Lisa; Hiew, Valerie; Hong, Johnson; Tu, Danny; Ward, Joanna; Gengatharen, Sonia; Barbosa, Leonel Ximenes; Mackey, David A
<x xml:space="preserve">Abstract</x> Purpose The aim was to compare the power of spectacles donated to a recycled spectacle program to the custom‐made spectacle refractive prescriptions dispensed in a developing country. Methods Two hundred consecutive prescriptions were audited in an optical dispensary in Timor‐Leste, a developing nation. These refractions were compared against measurements of 2, 075 wearable donated spectacles. We determined how many of the 200 prescriptions could be matched to a donated spectacle measurement, how many donated spectacles could be tried for each prescription and how long it would take to find the matched spectacles. Results There were 1, 854 donated spectacles identified as being suitable for comparison with the 200 refractive prescriptions. Twenty‐nine out of 200 prescriptions (14.5 per cent) were matched to at least one pair of donated spectacles. Conclusion Recycling all spectacles is not cost‐effective in a developing country that has the ability to make custom‐made spectacles and dispense ready‐made spectacles.